2011
DOI: 10.1016/j.jcrs.2010.12.060
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of posterior capsule opacification with hydrophobic acrylic and hydrophilic acrylic intraocular lenses

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
4
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 45 publications
3
58
4
4
Order By: Relevance
“…Table 1 summarises the contributions of all these studies. As shown, the higher PCO scores have been reported for IOLs made of hydrophilic acrylic material 1 4 5 13. Hollick et al 21 demonstrated several years ago that the presence of LECs on the posterior capsule after cataract surgery was considerably lower with polyacrylic IOLs than Poly(methyl methacrylate) (PMMA) or silicone IOLs.…”
Section: Discussionmentioning
confidence: 95%
“…Table 1 summarises the contributions of all these studies. As shown, the higher PCO scores have been reported for IOLs made of hydrophilic acrylic material 1 4 5 13. Hollick et al 21 demonstrated several years ago that the presence of LECs on the posterior capsule after cataract surgery was considerably lower with polyacrylic IOLs than Poly(methyl methacrylate) (PMMA) or silicone IOLs.…”
Section: Discussionmentioning
confidence: 95%
“…Vasavada et al 18 compared the incidence of PCO between hydrophobic acrylic (AcrySof IQ SN60WF, Alcon Laboratories, Inc.) and hydrophilic acrylic IOLs (Akreos Adapt, Bausch & Lomb). In the case of AcrySof IQ SN60WF IOL that has the same hydrophobic acrylic material and haptic design as our toric IOL, the incidence of PCO requiring an Nd:YAG capsulotomy was 0%.…”
Section: Discussionmentioning
confidence: 99%
“…However, PCO may progresses significantly with time and is more extensive following polymethylmetacrylate IOL implantation, while its progression rate after silicone and acrylic IOL implantation is low (19) . Previous reports have shown that hydrophilic IOLs lead to at least twice the number of Nd:YAG laser treatments when compared with hydrophobic lenses (1,13,17,18) . Although Nd:YAG laser capsulotomy is the standard treatment for PCO and is generally found to be safe and effective, it is also expensive and not free of complications (1,11,20) , including a significant rate of morbidity from postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that a hydrophobic lens ma terial causes less PCO than a hydrophilic material, even though the latter is more uveal biocompatible (17,18) . However, PCO may progresses significantly with time and is more extensive following polymethylmetacrylate IOL implantation, while its progression rate after silicone and acrylic IOL implantation is low (19) .…”
Section: Discussionmentioning
confidence: 99%